2020
DOI: 10.1088/1757-899x/915/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the wear resistance and resource hardened by electrospark machining of the cutting surfaces of the fingers of the headers of combine harvesters

Abstract: The article presents the technology of hardening the fingers of the reapers of combine harvesters by electrospark processing. To strengthen the cutting surfaces of the fingers, it is recommended to use an amorphous alloy grade 84KXSR. The operational tests presented in the work showed that wear and dulling of both serial products and experimental parts with electric spark coatings is characterized by two stages: running-in and natural wear. The running-in occurs during the running time of the fingers in 1 ha. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…On it was placed an indentor (counter-sample) in the form of a ball with a diameter of 6 mm composed of 100Cr6. The endurance of the investigated coatings was evaluated in conjunction with the counter-model [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…On it was placed an indentor (counter-sample) in the form of a ball with a diameter of 6 mm composed of 100Cr6. The endurance of the investigated coatings was evaluated in conjunction with the counter-model [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…This can affect energy and raw material losses. The results of operational tests have shown that the application of wear-resistant electrospark coating on the working bodies can improve their wear resistance and reliability of the machines, and increase their service life [14].…”
Section: Introductionmentioning
confidence: 99%